Evaluating a new obesity indicator for stroke risk prediction: comparative cohort analysis in rural settings of two nations - Feifei Yao; Jing Cui; Yuncheng Shen; Yuting Jiang; Yuanyuan Li; Xiaona Liu; Hongqi Feng; Zhe Jiao; Chang Liu; Fulan Hu; Wei Zhang; Dianjun Sun (BMC, 2024)
Abstract Background While the TyG index has been studied in relation to stroke risk, there is a lack of research integrating fat distribution indicators like Body Roundness Index (BRI) and Fat Mass Index (FMI). Additionally, comparative studies across multiple regions are scarce. This study investigates the association between obesity-related parameters and stroke incidence, examining the mediation effects of multimorbidity, using data from rural areas in China and the United Kingdom. Methods This cohort study included 60,685 participants (6,980 from China and 53,705 from UK). The obesity-related parameters were calculated using established formulas. The TyG index was determined as ln [TG (mg/dL) × GLU (mg/dL) / 2]. Additionally, composite indices were created by multiplying the TyG index by BMI, WC, FMI, and RBI to assess obesity-related risks. Cox regression analyses were employed on the relationship between Triglyceride Glucose index related parameters and stroke risk. Multiple mediation analysis was applied to assess the contributions of multimorbidity to obesity indicators in stroke occurrence. Results After excluding those who developed stroke within two years of enrollment, the Chinese cohort (6,638 subjects, median follow-up 4.33 years) had 237 ischemic and 21 hemorrhagic strokes. The UK cohort (53,631 subjects, median follow-up 13.85 years) had 742 ischemic and 316 hemorrhagic strokes. Chinese residents had lower BMI but higher visceral obesity (BRI), higher prevalence of multimorbidity, and higher stroke incidence compared to UK residents. Cox analyses demonstrated significant associations between BMI/TyG indices and ischemic stroke in both Chinese and UK populations, which diminished after adjusting for multimorbidity. In the Chinese rural cohort, only TyG-BRI (HR:1.13, 95%CI:0.99-1.30) approached statistical significance after full adjustment for mediators. In contrast, in the UK cohort, significant associations persisted for most TyG Index indicators when full adjustment for mediators, including BMI (HR: 1.17, 95% CI: 1.09-1.26), TyG-BMI (HR: 1.16, 95% CI: 1.07-1.26), TyG-WC (HR: 1.13, 95% CI: 1.03-1.25), TyG-FMI (HR: 1.17, 95% CI: 1.07-1.28), and TyG-RBI (HR: 1.15, 95% CI: 1.06-1.24). TyG-BRI also showed the best predictive performance for ischemic stroke in Chinese rural residents (AUC > 0.7) and exhibited an almost linear relationship with ischemic stroke occurrence. Additionally, TyG-BRI presented a U-shaped relationship with the risk of hemorrhagic stroke incidence in the UK (p overall = 0.041, p non-linear = 0.017). Multimorbidity mediated the relationship between TyG indices, and ischemic stroke incidence in both cohorts. The mediation percentage for multimorbidity was higher than the sum of individual chronic diseases, with a higher mediation percentage in the Chinese cohort (up to 51%) compared to the UK cohort (up to 27.2%). Conclusions Chinese rural residents exhibit higher levels of visceral obesity compared to residents in UK, leading to greater stroke susceptibility mediated by multimorbidity. These findings underscore the importance of comprehensive management of multimorbidity for stroke prevention. The TyG-BRI may serve as a promising predictor of ischemic stroke incidence among rural community residents.